Legal realism regained saving realism from critical acclaim - De Been, Wouter, 1966- (Stanford, Calif. : Stanford Law, 2008)
This title presents a comparison between the legal realists, a group of pragmatic legal theorists from the 1920s and 1930s, and critical legal studies, a movement of postmodern legal theory during the end of the 20th century. It argues for a return to legal realism and the classical pragmatism of John Dewey and William James, and for a rejection of the postmodern critique of critical legal studies.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Philosophy; Law